Construction and testing of a bacterial luciferase reporter gene system for in vivo measurement of nonsense suppression in Streptomyces - Weiser, J; Buriánková, K; Kalachová, L; Branny, P; Pernodet, J L (Folia microbiologica, 2006)
A reporter gene system, based on luciferase genes from Vibrio harvei, was constructed for measurement of translation nonsense suppression in Streptomyces. Using the site-directed mutagenesis the TCA codon in position 13 of the luxB gene was replaced by all of the three stop codons individually. By cloning of luxA and luxB genes under the control of strong constitutive Streptomyces promoter ermE* in plasmid pUWL201 we created Wluxl with the wild-type sequence and pWlux2, pWlux3 and pWlux4 plasmids containing TGA-, TAG- and TAA-stop codons, respectively. Streptomyces lividans TK 24 was transformed with the plasmids and the reporter system was tested by growth of the strain in the presence of streptomycin as a translation accuracy modulator. Streptomycin increased nonsense suppression on UAA nearly 10-fold and more than 20-fold on UAG. On the other hand, UGA, the most frequent stop signal in Streptomyces, the effect was negligible.
Keywords: Protein Synthesis Inhibitors; Streptomyces lividans; luciferasy bakteriální; reportérové geny; Promoter Regions, Genetic; methyltransferasy; Codon, Nonsense; Mutagenesis, Site-Directed; nesmyslný kodon; Genes, Suppressor; bakteriální geny; proteosyntéza; Methyltransferases; Protein Biosynthesis; supresorové geny; streptomycin; Bacterial Proteins; mutageneze cílená; Genes, Reporter; Plasmids; promotorové oblasti (genetika); Streptomycin; plazmidy; Genes, Bacterial; Luciferases, Bacterial; inhibitory syntézy proteinů; bakteriální proteiny